K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

26 tháng 11 2021

-30 + ( 25 - x) = -1

           25 - x = -1 - ( - 30)

           25 - x = 29

                  x = 29-25

                  x = 4

8 tháng 2 2019

Trả lời zùm đi

8 tháng 2 2019

éo biết

10 tháng 2 2021

 15-(4-x)=6

⇒15-4+x=6

⇒11+x=6

⇒x=-5

 x-(12-25)=-8

⇒x+13=-8

⇒x=-21

(x-29)-(17-38)=-9

⇒x-29+21=-9

⇒x-8=-9

⇒x=-1

 -30+(25-x)=-1

⇒-30+25-x=-1

⇒-5-x=-1

⇒x=-4

12 tháng 1 2022
GÝYGIVJGGGFHZGHBBC
5 tháng 12 2017

a) 315 + 2x = x+115

<=> 2x-x = 115-315

<=> x = -200

Vậy x= -200

5 tháng 12 2017

b) 25-(30-x)=25-(-12+125)

<=> 25-30+x = -88

<=> -5 + x =-88

<=> x = -83

Vậy x=-83

27 tháng 6 2018

a ) 126 - 2x = 12 - ( -28 )

     126 - 2x = 40

     2x = 126 - 40

     2x = 86 

     x = 86 : 2

     x = 43

b ) 25 - 5( x + 1 ) = 30 - 125

     25 - ( 5x + 5 ) = -95

     25 - 5x - 5 = -95

     20 - 5x = -95

     5x = 20 - ( - 95 )

     5x = 115

     x = 115 : 5

     x = 23

c ) I 3x - 1 I - 25 = 73 

     I 3x - 1 I = 73 + 25

     I 3x - 1 I = 98

=> 3x - 1 = 98 hoặc 3x - 1 = -98

=> 3x = 98 + 1 hoặc 3x = -98 + 1

=> 3x = 99 hoặc 3x = -97

=> x = 99 : 3 hoặc x = -97 : 3 

=> x = 33 hoặc x = -93/3

d ) 2( x + 2 ) - 6 = 120 - 4x 

     2x + 4 - 6 = 120 - 4x 

     2x - 2 = 120 - 4x

     2x + 4x = 120 + 2

     6x = 122

     x = 122 : 6

     x = 61/3

27 tháng 6 2018

a) x = 43

b) x = 23

c) x = 33 hoac x= -97/3

a) 15 – ( 4 – x) = 6 

=>  4 – x= 15 - 6

=>  4 – x= 9

=>  x= 4 - 9 

=>  x= -5

10 tháng 2 2020

Easy!

a) \(15-\left(4-x\right)=6\)

\(\Leftrightarrow4-x=15-6\)

\(\Leftrightarrow4-x=9\)

\(\Leftrightarrow x=4-9\)

\(\Leftrightarrow x=-5\)

Vậy \(x=-5\)

b) \(-30+\left(25-x\right)=-1\)

\(\Leftrightarrow\left(25-x\right)=-1-\left(-30\right)\)

\(\Leftrightarrow25-x=29\)

\(\Leftrightarrow x=25-29\)

\(\Leftrightarrow x=-4\)

c) \(x-\left(12-25\right)=-8\)

\(\Leftrightarrow x-\left(-13\right)=-8\)

\(\Leftrightarrow x=-8+-13\)

\(\Leftrightarrow x=-21\)

Vậy \(x=-21\)

d) \(\left(x-29\right)-\left(17-38\right)=-9\)

\(\Leftrightarrow\left(x-29\right)-\left(-21\right)=-9\)

\(\Leftrightarrow x-29=-9+\left(-21\right)\)

\(\Leftrightarrow x-29=-30\)

\(\Leftrightarrow x=-30+29\)

\(\Leftrightarrow x=-1\)

Vậy \(x=-1\)

17 tháng 1 2017

4 - x =15 - 6

4 - x = 9

     x= 4-9

     x=-5

25-x=-1--30

25-x=29

    x=25-29

    x=-4

ai tk minh minh tk lai

17 tháng 1 2017

A/  \(15-\left(4-X\right)=6\)

\(15-4+X=6\)

\(11+X=6\)

\(X=6-11\)

\(X=-5\)

B/   \(-30+\left(25-X\right)\)\(=-1\)

\(-30+25-X=-1\)

\(-5+X=-1\)

\(X=-1+5\)

\(X=4\)